Effectiveness of reservoir length on electromigration lifetime enhancement for ULSI interconnects with advanced technology nodes - Tan, Cher Ming (2013)
Reservoir length in ULSI interconnections can enhance their electromigration lifetime. As low-K dielectric is employed in current technology node, and line current density and temperature increase as we advanced in technology node, we investigate the impact of the above-mentioned on the effectiveness of reservoir length. We found that current density has no impact at all, but higher line temperature improves the effectiveness. As for the low-K dielectric used, most of them do not affect the effectiveness except CDO which degrade its effectiveness. In all cases, the saturation length where the enhancement ceases remain at around 50 nm, and it is not affected by the above-mentioned parameters.